THE NOVEL “RADETZKY MARCH” BY JOSEPH ROTH AS INTERTEXT - Monolatiy, T. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article substantiates the thesis that the most famous novel by J. Roth “Radetzky March” has intertextual basis gleaned from «family chronicles» of that time. Argued that the novel contains some intertextual inclusions: the last descendant of an influential family; isolation of the protagonist from his ancestors; dichotomy “metropolis” / “province”; disillusionment and non-heroic death; aesthetics of decline / personal reasons for the decline. As writer’s view at the specifics of the prose works determinates the appearing of a peculiar world, one of his basic principles was artistic objectivity. The author shows both the external and the internal world of his characters, bringing in his own experiences. It’s proved that the novel is more implication of the author’s critics of modernity than nostalgia for better times, expressed through intertextual influences of German and English literature, as well as allusions to the works of the Austrian, French, Polish and Czech writers.